Influência do teor de silício em filmes finos de nitreto de zircônio depositados por magnetron sputtering reativo - Freitas, Flávio Gustavo Ribeiro (2016)
Zr-Si-N thin films were deposited by reactive magnetron sputtering to study silicon influence in the structure, morphology and properties such as hardness and oxidation resistance. Six thin films with silicon concentrations from 2.8 to 14.9 at.% were selected. Thin films morphology shows that there are no columnar grains, structure that is commonly observed in films deposited by sputtering. It was identified amorphous and crystalline areas in films microstructure, creating a structure composed by crystalline grains embedded in an amorphous phase, which were characterized by EDS as Zr and Si rich areas, respectively. XRD results indicate ZrN peaks intensity reduction and a broadening increase due silicon nitride segregation to grain boundaries, which is responsible for grain size reduction, that was calculated by Scherrer and reached magnitudes lower than 10 nm. XRD peaks displacement are observed for all samples and it can be explained due formation of a solid solution in which Si replaces Zr atoms in ZrN crystal lattice and due a strong interface between crystalline phase and amorphous one. XPS data reinforce the presence of compounds like ZrN and Si3N4 and it is also possible to infer the formation of a solid solution of Si in ZrN lattice. Oxidation tests were performed at temperatures in the range of 500°C to 1100°C. ZrN film is almost fully oxidized at 500°C, while films with high silicon content maintain ZrN grains stable at 700°C. When oxidized, ZrN films form monoclinic ZrO2 phase, but, in films with silicon addition, the stable phase is the tetragonal one. This happens due ZrN grain size reduction, because tetragonal phase has the lowest surface energy. Oxidation tests results confirm that there is a mechanism acting as diffusion barrier in films, preventing grains coalescence and oxygen diffusion into film structure. This mechanism is a direct consequence of silicon segregation process to grain boundaries, which ensures the formation of a nanostructure composed of ZrN grains embedded by an amorphous Si3N4 layer (nc-ZrN/a-Si3N4), allowing oxidation resistance improvement in at least 200°C.